DEVELOPING INSURANCE INVESTMENTS BASED ON ESG AND GREEN FINANCE STANDARDS IN LOCAL AND GLOBAL MARKETS (American Journal of Business Management, Economics and Banking, 2025)
In the insurance sector, the integration of ESG (Environmental, Social and Governance) standards and green finance concepts is becoming increasingly important in increasing the sustainability of investment portfolios. Investment management processes based on these principles are developing in global and local markets, helping to reduce environmental risks and strengthen social responsibility. Green bonds, climate funds and other green financial instruments are emerging as key tools for insurance companies to implement sustainable investment strategies. Thus, ESG and green finance standards are improving the financial performance of insurance investments and contributing to sustainable development goals.